A comparative analysis of Center for Independent Living staff and board of directors regarding CIL services and consumer participation. Issue 2 (3rd April 2017) - Ravesloot, Craig; White, Glen W.; Gonda-Kotani, Chiaki; Shinnick, Kelsey
ABSTRACT: Community living of people with disabilities spans independent living and community engagement. Consumer choice and control of their level of community participation requires community accessibility, resources and supports. Some people with disabilities have difficulties procuring and maintaining these resources. Centers for Independent Living (CIL) are advocacy and service agencies that have been empowering consumers to meet their needs for over 40 years. Despite this history, little is known about the value of CIL services for increasing community participation of people with disabilities. We administered the CIL Participation Service Survey to 420 CIL staff members and 107 CIL board members to examine their opinions about the relative value of different CIL services for increasing community participation of their consumers. Results indicated that both staff and board members have very high regard for the value and quality of CIL services. The Independent Living (IL) philosophy of consumer choice and control was among the most highly rated aspects of CIL service delivery for both staff and board members. Overall, staff and board member responses were very consistent in terms of the top-rated strengths and weaknesses of CIL services for increasing participation among consumers. Differences appeared to reflect the daily staff focus on specific consumer need versus board members' view of larger community issues.